2021
DOI: 10.1007/s40266-021-00880-4
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Tuberculosis in Older Adults: Increased Mortality Related to Tuberculosis Within Two Months of Treatment Initiation

Abstract: Background The proportion of tuberculosis (TB) patients who are older adults is increasing worldwide. Nearly 60% of TB patients in Japan are 70 years or older, and the TB incidence rate in Japan is one of the highest among high-income countries. The previous TB treatment guidelines prior to 2018 in Japan recommended excluding pyrazinamide (PZA) from the initial regimen for patients aged over 80 years. Objectives We aimed to examine differences in TB treatment outcomes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 16 publications
(19 reference statements)
1
18
0
2
Order By: Relevance
“…Because pyrazinamide is most frequently responsible for liver damage [62,65,66], the American Thoracic Society, the Centers for Disease Control and Prevention and the Infectious Diseases Society of America assess that in the elderly with a moderate TB disease with low risk of drug resistance, the benefits of pyrazinamide use in the initial dosing regimen is less than the risk of serious adverse events [62,67]. Therefore, American guidelines do not recommend the use of pyrazinamide during the intensive phase in patients aged >75 years for moderate disease and low resistance risk [68,69]. In this setting, the initial regimen consists of isoniazid, rifampicin and ethambutol.…”
Section: Treatment Tolerancementioning
confidence: 99%
“…Because pyrazinamide is most frequently responsible for liver damage [62,65,66], the American Thoracic Society, the Centers for Disease Control and Prevention and the Infectious Diseases Society of America assess that in the elderly with a moderate TB disease with low risk of drug resistance, the benefits of pyrazinamide use in the initial dosing regimen is less than the risk of serious adverse events [62,67]. Therefore, American guidelines do not recommend the use of pyrazinamide during the intensive phase in patients aged >75 years for moderate disease and low resistance risk [68,69]. In this setting, the initial regimen consists of isoniazid, rifampicin and ethambutol.…”
Section: Treatment Tolerancementioning
confidence: 99%
“…In a study by Abbara A et al, 11 Miliary mottling (4.1%) was common radiological feature in elderly patients while Cavitaiton on chest radiograph was in 27 % and 40% respectively in studies by Hase I et al 12 and Elineni JL. 13 As ZN staining was the primary modality for diagnosis of tuberculosis in our study.…”
Section: Discussionmentioning
confidence: 92%
“…Our finding reported that the pulmonary TB mortality rate among participants aged ≥70 years was higher than that among those aged <70 years which was compatible with recent evidence from Japan indicating that patients aged ≥75 years with pulmonary TB experienced increased mortality related to TB during treatment. (22) However, another report in Thailand presented that older patients were not associated with unsuccessful pulmonary TB outcomes including death, default, treatment failure, and transfer due to multidrug-resistant TB. (23) We found that individuals with first follow-up sputum AFB positive had a higher mortality rate when compared with those with first follow-up sputum AFB negative.…”
Section: Discussionmentioning
confidence: 99%